Fungal arthritis secondary to Colletotrichum gloeosporioides. Issue 1 (February 2015) - Cho, Jonathan C.; Sharma, Rajendra S.; Sutton, Deanna A.; Wiederhold, Nathan P.; Sanders, Carmita; Wickes, Brian L.; Estrada, Sandy J.
Abstract : Introduction: Colletotrichum spp. are common plant‐pathogenic fungi that usually occur as asymptomatic endophytes on aerial organs of host plants. Of the many Colletotrichum spp. described, only four have been associated with infections in humans, one of these being Colletotrichum gloeosporioides . Case presentation: Infections cited in humans due to Colletotrichum spp. typically involve the eye (keratitis/keratomycosis/endophthalmitis) or are subcutaneous in nature and secondary to trauma. We report a clinical case of septic arthritis caused by Colletotrichum gloeosporioides in an immunocompetent 55‐year‐old male. DNA sequencing was performed for identification of the organism. Antifungal susceptibility testing was performed according to the Clinical and Laboratory Standards Institute M38‐A2 standard for broth microdilution testing against filamentous fungi. Conclusion: To the best of our knowledge, this is the first case of a Colletotrichum sp., specifically Colletotrichum gloeosporioides, causing septic arthritis in humans. This report highlights the successful treatment of a case of septic arthritis due to Colletotrichum gloeosporioides with voriconazole.